2021
DOI: 10.1080/02770903.2021.1938603
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of glycopyrrolate administered by metered dose inhaler in patients with uncontrolled asthma despite ICS/LABA treatment

Abstract: Objective: To evaluate the efficacy and safety of three doses of glycopyrrolate metered dose inhaler (GP MDI) in patients with uncontrolled asthma despite treatment with inhaled corticosteroid/long-acting β 2 -agonists (ICS/LABA) with or without tiotropium, to characterize the benefit of triple therapy. Method: This phase II/III, double-blind study randomized patients to 24 weeks' treatment with twice-daily GP MDI 36 µg, 18 µg, 9 µg, or placebo MDI (all delivered via Aerosphere inhalers), or once-daily open-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A subgroup of patients received open-label TioR (2.5 mg once daily) as an add-on to ICS plus LABA. 48 The primary end point of change from baseline in FEV 1 area under the curve from 0 to 4 hours at week 24 was nominally significant in the 9-mg glycopyrronium group versus the placebo group and the open-label tiotropium group. A post hoc analysis identified a dose-related response to glycopyrronium when alternative definitions of baseline FEV 1 (using postbronchodilator FEV 1 and taking the mean of prebronchodilator FEV 1 from visits 3 and 4) were used in the analysis.…”
Section: Lama Plus Ics Plus Laba (Open Triple Therapy) Versus Ics Plu...mentioning
confidence: 87%
See 3 more Smart Citations
“…A subgroup of patients received open-label TioR (2.5 mg once daily) as an add-on to ICS plus LABA. 48 The primary end point of change from baseline in FEV 1 area under the curve from 0 to 4 hours at week 24 was nominally significant in the 9-mg glycopyrronium group versus the placebo group and the open-label tiotropium group. A post hoc analysis identified a dose-related response to glycopyrronium when alternative definitions of baseline FEV 1 (using postbronchodilator FEV 1 and taking the mean of prebronchodilator FEV 1 from visits 3 and 4) were used in the analysis.…”
Section: Lama Plus Ics Plus Laba (Open Triple Therapy) Versus Ics Plu...mentioning
confidence: 87%
“…75 Furthermore, if neuronal plasticity is considered to be a treatable trait, it may be warranted to consider triple therapy earlier than currently recommended by the GINA report; however, this therapeutic approach must be confirmed in appropriately statistically powered clinical trials. 76 In clinical trials in patients with inadequately controlled asthma with ICS plus LABA (see Table E4 in this article's Online Repository at www.jacionline.org), 42,[46][47][48] the addition of a LAMA resulted in a significant improvement in peak FEV 1 42 and trough FEV 1 , 42,47 ACQ-7 score, 42 and in-clinic trough PEF rate, 47 increased the time to first severe exacerbation, 42 and provided modest sustained bronchodilation. 42 A post hoc analysis of 2 of these studies 42 showed that compared with placebo the efficacy of add-on TioR to ICS plus LABA is independent of baseline characteristics, including age, sex, body mass index, disease duration, age at asthma onset, smoking status, allergic status, and FEV 1 reversibility.…”
Section: Lama Plus Ics Plus Laba (Open Triple Therapy) Versus Ics Plu...mentioning
confidence: 99%
See 2 more Smart Citations